Debt to Equity Ratio, Net Profit Margin, dan Earning Per Share Terhadap Harga Saham Non Perbankan yang Terdaftar dalam Indeks IDX30 di Bursa Efek Indonesia Tahun Periode 2020-2022 - Rahayu Rahayu; Yenny Ernitawati; Nasiruddin, Nasiruddin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The share price is the price of a share that investors must consider when making an investment because the share price of a company is a reflection of the company's achievements and value. This research aims to determine the influence of Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Earning Per Share (EPS) partially and simultaneously on stock prices. This type of research is associative quantitative research using secondary data collection techniques. The population of this research is non-banking companies listed on the IDX30 index on the Indonesia Stock Exchange in 2020-2022 with a sampling technique using purposive sampling technique so that a sample of 23 companies that meet the criteria is obtained. The data analysis technique used is descriptive statistical analysis, classical assumption testing, multiple linear regression analysis and hypothesis testing. Based on partial and simultaneous tests, it can be concluded that DER and NPM partially have a negative and insignificant effect on stock prices, while EPS has a positive and very significant effect on stock prices. And DER, NPM, and EPS simultaneously have a positive and very significant effect on stock prices.